2017
DOI: 10.1504/ijitm.2017.10001027
|View full text |Cite
|
Sign up to set email alerts
|

A situation awareness analysis scheme to identify deficiencies of complex man-machine interactions

Abstract: Abstract:This paper presents an analysis scheme which aims to support a systematic study of required situation awareness (RSA). This scheme supports identification of deficiencies of support for situation awareness (SA). Information needs are goal and task dependent and can be defined using existing cognitive task analysis (CTA) methods. RSA, however, is a subset of information needs and depends on the interaction between goals, tasks, system factors and individual factors. The analysis scheme has helped to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Van Doorn et al (2017) showed that proper information visualization is required to allow operators to correctly access and process the information presented by the systems and to obtain the necessary SA. More specifically, the collected research data indicated that differences in the form of information visualization by the different systems used for the same tasks may lead to errors in SA.…”
Section: Defining the Coherent User Interface Conceptmentioning
confidence: 99%
See 4 more Smart Citations
“…Van Doorn et al (2017) showed that proper information visualization is required to allow operators to correctly access and process the information presented by the systems and to obtain the necessary SA. More specifically, the collected research data indicated that differences in the form of information visualization by the different systems used for the same tasks may lead to errors in SA.…”
Section: Defining the Coherent User Interface Conceptmentioning
confidence: 99%
“…Therefore, designing an integrated UI requires defining information needs as sets per task. In Van Doorn et al (2017), we described task analysis steps required to generate an information needs overview. As in the case of coherent interfaces, the information contents (pieces of information) required for each task and the overlap of information (i.e., the information which is needed for multiple tasks) can be specified by the means of set theory, see Fig.…”
Section: Defining the Coherent User Interface Conceptmentioning
confidence: 99%
See 3 more Smart Citations